The concise Oxford dictionary of music - Kennedy, Michael, 1926-2014 (Oxford University Press, 1980)
"The Concise Oxford Dictionary of Music is the most authoritative and up-to-date dictionary of music available in paperback. Coverage includes musical terms from allegro to zingaro, and musical works from Aida to Zauberflote, as well as composers, librettists, musicians, singers, and orchestras. It provides a mine of information for all lovers of music." "The book includes musical instruments and their history; and covers living composers and performers, with over 150 added for this edition."--BOOK JACKET.